2009
DOI: 10.4012/dmj.28.212
|View full text |Cite
|
Sign up to set email alerts
|

Bite force measurement system using pressure-sensitive sheet and silicone impression material

Abstract: This study was conducted to reduce the bias in measured values caused by the thickness of materials used in occlusal examinations. To this end, a silicone impression material for bite force measurement and an experimental model of a simplified stomatognathic system were employed in this study. By means of this experimental model, results showed that the effect of bias toward the posterior arch could be reduced in the anterior-posterior distribution of bite forces and in the occlusal contact areas due to the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 17 publications
0
16
0
2
Order By: Relevance
“…19 Moreover, its performance is not dependent on the proficiency of the examiner, and it is simple to use for objective evaluation of occlusal function. 12 In a previous study, occlusal contact area and force were reported to be greater in male patients than in female patients. Further, the occlusal contact area was reported to be larger in patients aged 40 years, while there was no statistically significant difference in the occlusal contact area among the three age groups (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and 31-40 years).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…19 Moreover, its performance is not dependent on the proficiency of the examiner, and it is simple to use for objective evaluation of occlusal function. 12 In a previous study, occlusal contact area and force were reported to be greater in male patients than in female patients. Further, the occlusal contact area was reported to be larger in patients aged 40 years, while there was no statistically significant difference in the occlusal contact area among the three age groups (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and 31-40 years).…”
Section: Discussionmentioning
confidence: 89%
“…9 One study suggested possible discrepancies between results from dental casts and the actual occlusal contact during functional occlusion. 10 The Dental Prescale system (Fuji Film Corp, Tokyo, Japan) has been widely used to evaluate occlusal contact area and force due to its simplicity and objectivity, [11][12][13] but the scope of the research using this system has been limited to posttreatment changes during short-term follow-up over 1 year without consideration of pretreatment records.…”
Section: Introductionmentioning
confidence: 99%
“…Different occlusal indicators can be used during prosthodontic treatment for diagnosis and treatment purposes [16]. Qualitative indicators (articulating paper and articulating silk) can measure only the location and number of tooth contacts while quantitative indicators (electro-optic and resistive techniques such as T-scan) can measure the time and force characteristics of tooth/teeth contact [17]- [19].…”
Section: Discussionmentioning
confidence: 99%
“…During an occlusal examination, the accurate measurement of tooth contacts can provide valuable information for diagnostic, treatment or prognostic purposes (1). Currently, this is achieved using occlusal indicators (or ‘bite registration’ strips) that are important tools in locating interferences and refining occlusal contacts during prosthodontic treatments (2).…”
Section: Introductionmentioning
confidence: 99%